Risk of Depression, Anxiety, and Stress During the Second Wave of COVID-19 in Slovenia - Rus Prelog, Polona; Matić, Teodora; Pregelj, Peter; Sadikov, Aleksander (Frontiers in Psychiatry, 2022)
The spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) causing coronavirus disease 2019 (COVID-19) pandemic has led to numerous negative consequences on the mental health of the population throughout the world. The main aim of our study was to compare the risk for depression, anxiety, and stress during the second wave of the pandemic in Slovenia. An additional goal was to analyze the association of depression, anxiety, and stress, with the most relevant subjective factors that define the quality of life. Furthermore, we aimed at determining whether health workers have a higher risk for depression following the course of the pandemic. The study was conducted on the general population, between July 2020 and January 2021 through an online survey. The data of 1,728 respondents in two samples of respondents (782 at baseline -- first measurement point and 946 during the second measurement point) of the second wave were analyzed using zero-inflated negative binomial regression and Mann-Whitney U-test. The findings of this study show that the rise the second wave was associated with a higher risk for depression, anxiety and stress. The risk for all three was higher for younger participants. Women showed a higher risk for anxiety and stress. Finances, relationships, and housing dissatisfaction were relevant predictors for depression, anxiety and stress. Health workers in our sample showed a higher risk for stress, but not for depression or anxiety, than the general population. Our findings highlight the urgent need for coordinating and developing mental health services and tailored interventions to reduce the mental health burden, especially in the younger.